Exclusion and poverty: An analytical approach for understanding exclusion and assessing programmes targeting the very poor in Bangladesh - Zohir, Sajjad; Rabbani, Mehnaz; Mallik, Biva Arani; Huq, Iftekharul; Afsana, Raisa (BRAC Research and Evaluation Division, 2022)
Exclusion is a term that comes up often in association with poverty, social welfare and social injustice. Development interventions are designed with some notion of benefiting or including the excluded. This paper analyses the concept of exclusion using simple demand-supply tools. A simple framework is proposed, that separates the attributes and spaces of exclusion to help in assessing development interventions. Success of programmes may be scaled in terms of their achievements in making poor included in the mainstream (i.e. main product/service space), or in a segmented space (from either complete exclusion or from previous inclusion in lower quality space), or not being able to include the poor in relevant spaces in any meaningful way. The case of hardcore poverty is investigated to understand the different approaches used to address the exclusion, and the underlying assumptions made regarding the attribute-space links of exclusion. The case studies undertaken are meant to propose a simple framework of evaluating programmes targeting poor and/or hardcore poor, which is consistent with the analytical framework proposed.